1968
DOI: 10.1172/jci105932
|View full text |Cite
|
Sign up to set email alerts
|

Renal accumulation of salicylate and phenacetin: possible mechanisms in the nephropathy of analgesic abuse

Abstract: A B S T R A C T Since either aspirin or phenacetin might be causative in the nephropathy of analgesic abuse, studies were designed to examine the renal accumulation and distribution of the major metabolic products of these compounds, salicylate and N-acetyl-p-aminophenol (APAP) respectively, in dogs. Nineteen hydropenic animals were studied, of which seven were given phenacetin, nine received acetyl salicylic acid, two were given both aspirin and phenacetin, and one received APAP directly. Two of three hydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
2

Year Published

1970
1970
1991
1991

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(20 citation statements)
references
References 16 publications
(15 reference statements)
1
16
1
2
Order By: Relevance
“…Such distribution of lesions could be explained if the offending drugs were concentrated in the kidney tissue. Bluemle and Goldberg reported that they could find no difference in salicylate concentration between cortex and medulla in the dog kidney (33) in contradiction with our results. Salicylate in our studies was concentrated in the medulla by a factor of 1.5-3 with respect to the cortex.…”
Section: Discussioncontrasting
confidence: 99%
“…Such distribution of lesions could be explained if the offending drugs were concentrated in the kidney tissue. Bluemle and Goldberg reported that they could find no difference in salicylate concentration between cortex and medulla in the dog kidney (33) in contradiction with our results. Salicylate in our studies was concentrated in the medulla by a factor of 1.5-3 with respect to the cortex.…”
Section: Discussioncontrasting
confidence: 99%
“…When animals are fed phenacetin, it is para cetamol that is concentrated in the renal papilla [7], In the aspirin, phenacetin, caffein, mixture replacement of phenacetin by an equivalent dose of paracetamol does not alter the incidence and severity of RPN in animal studies [8][9][10]. Animal experiments have shown that para cetamol alone can cause RPN, although in high doses (3,000 mg/kgdaily) [8].…”
Section: Discussionmentioning
confidence: 99%
“…49], Pre sumably. the papillary necroses are attributable to toxic effects of PH metabolites which are found in a high con centration within the papilla [6], Although the exact pathogenetic mechanisms are so far unknown, experi mental findings have implicated vascular damage [28].…”
Section: Discussionmentioning
confidence: 99%